(untitled) (Research, Society and Development, 2021)
Objectives: The aim of the present study was to evaluate oral health and motor function in children and adolescents with cerebral palsy (CP) and determine the perception of caregivers regarding the oral health status of these individuals. Study Design: A cross-sectional study was conducted with 35 children/adolescents with CP and their caregivers. A questionnaire was administered to the caregivers addressing the oral health of the individuals with CP. The dmft/DMFT index, visible plaque index, malocclusion, dental age, pH, buffering capacity and flow salivary were determined. Motor function was evaluated using the GMFCS and GMFM-88 instruments. Results: A significant association was found between the GMFCS category and malocclusion. The GMFM-88 index was significantly lower in individuals with malocclusion and an altered dental age. Caregivers of quadriplegic individuals (57.1%), wheelchair users (42.9%) and those with more severe gross motor impairment (GMFM-88) reported more oral problems. Conclusion: Malocclusion and dental age were associated with motor function in children/adolescents with cerebral palsy. The caregivers of children and adolescents who are quadriplegic, use a wheelchair and have greater impairment regarding gross motor function reported more oral problems.